Религиозная жизнь тюрко-мусульман Румынии в коммунистическую эпоху - Сейдаметов, Э.Х. (Культура народов Причерноморья, 2013)
В данной статье рассмотрены особенности религиозной жизни тюрко-мусульман
Румынии в коммунистическую эпоху. Данная тема является новой в отечественной историографии и
получила фрагментарное освещение в работах зарубежных исследователей. В результате анализа
показаны пертурбации в религиозной сфере, которая с приходом коммунистов была взята под жесткий
контроль государства. Негативными последствиями конфессиональной политики правящего режима
были аресты служителей культа, запрет на публичное совершение обрядов, конфискация вакуфных
земель и т.д. Созданные государством религиозные структуры служили агитационно-
пропагандистским целям правящей партии и слабо выражали интересы мусульманского населения
Румынии. У даній статті розглянуто особливості релігійного життя тюрко-мусульман Румунії в
комуністичну епоху. Дана тема є новою у вітчизняній історіографії і отримала фрагментарне
висвітлення у працях зарубіжних дослідників. У результаті аналізу показані пертурбації в релігійній
сфері, яка з приходом комуністів була взята під жорсткий контроль держави. Негативними наслідками
конфесійної політики правлячого режиму були арешти служителів культу, заборона на публічне
здійснення обрядів, конфіскація вакуфних земель і т.д. Створені державою релігійні структури служили
агітаційно-пропагандистським цілям правлячої партії і слабо виражали інтереси мусульманського
населення Румунії. This article describes the peculiarities of religious life of the Turkic-Muslims in Romania in the
communist era. This subject is new in the historiography of the country and it is partially investigated in the
works of foreign researchers. The analysis results show the perturbations in the religious sphere that was
brought under strict control of the government during the communists governing. Negative effects of
confessional policy of the governing regime were clergy arrests, the ban on public rituals performing,
confiscation of waqf land, etc. To keep Turkic-Muslims of Dobrudji under its auspices and take them under their
ideological control in 1944, the authorities developed "Muslim Democratic Union", which was not recognized
by the people. The educational establishments where priests were trained were eliminated in order to neutralize
the influence of Islam, to knock it out of the public consciousness and turn it only into a ritual component of the
religious life of the people, the personnel policy aimed at reducing the various positions of the clergy, which led
to the closure of many mosques and public prayer houses. The import of religious literature was banned,
pilgrimage to Mecca was forbidden as well as making contacts with the representatives of the Islamic
community in other countries. These and other measures led to the growth of religious illiteracy, the substitution
of the ideological basis for atheistic and materialistic. The religious structures formed by the government
presented agitation and propaganda purposes of the governing party and expressed insufficiently the interests of
the Muslim population of Romania.